Pelatihan Media Ajar Inovatif: Integrasi Video Animasi dan Permainan bagi Guru Sekolah Dasar - Purwasi, Lucy Asri; Alfian, Denny; Fitriyana, Nur; Elly, As; Mulyono, Dodik (LP4MK STKIP PGRI Lubuklinggau, 2025)
This training program aimed to enhance elementary school teachers' competencies in designing and utilizing instructional media that integrate technology and educational games. The program was conducted at SD Negeri 1 Embacang Baru and SD Negeri 2 Embacang Lama, Karang Jaya District, involving 25 participating teachers. The training was structured into five stages: needs assessment, conceptual training, media design practice, reflection and evaluation, and remote mentoring. The training content included the development of animated learning videos using Powtoon and the implementation of educational games such as LEGO and snakes and ladders. The results demonstrated high levels of engagement and enthusiasm among participants throughout all sessions. Based on self-assessment and satisfaction surveys, 80–90% of participants agreed or strongly agreed with all satisfaction indicators. Skill evaluations showed that most participant groups achieved ratings in the “Good” to “Very Good” categories. The training significantly improved teachers’ understanding, creativity, and confidence in developing effective, engaging, and curriculum-relevant instructional media.